SANDOR KATZ'S FERMENTATION JOURNEYS : RECIPES, TECHNIQUES, AND TRADITIONS FROM AROUND THE WORLD - Katz, Sandor Ellix, 1962- (London : Chelsea Green Publishing, 2021)
"For the past two decades, fermentation expert and bestselling author Sandor Katz has traveled the world, both teaching and learning about the many fascinating and delicious techniques for fermenting foods. Wherever he's gone, he has gleaned valuable insights into the cultures and traditions of local and indigenous peoples, whether they make familiar ferments like sauerkraut or less common preparations like natto and koji. In his latest book, Sandor Katz's Fermentation Journeys, Katz takes readers along with him to revisit these special places, people, and foods. This cookbook goes far beyond mere general instructions and explores the transformative process of fermentation through: detailed descriptions of traditional fermentation techniques; celebrating local customs and ceremonies that surround particular ferments; profiles of the farmers, business owners, and experimenters Katz has met on his journeys. Sandor Katz's Fermentation Journeys reminds us that the magical power of fermentation belongs to everyone, everywhere. Perfect for adventurous foodies, armchair travelers, and fermentation fanatics who have followed Katz's work through the years--from Wild Fermentation to The Art of Fermentation to Fermentation as Metaphor--this book reflects the enduring passion and accumulated wisdom of this unique man, who is arguably the world's most experienced and respected advocate of all things fermented." --
Includes index.
Keywords: Katz, Sandor Ellix, -- 1962- -- Travel; Fermented foods; Fermentation